Analysis of Students' Ability to Work on PISA Questions in Personal Context for Students of Grade IX SMPN - Rauf, Nurisnaeni; Nur, Fitriani; Putra, Rafli Permana; Munawarah,; Thalhah, Sitti Zuhaerah (Alauddin Journal of Mathematics Education, 2023)
PISA (Programme for International Student Assesment) is an international standard study conducted by OECD who assesing the literacy skills of 15-year-olds’ students which is followed by several participating countries,including Indonesia. The research aim to describe the problem solving ability of junior high school students in solving PISA’s mathematic problems personal context. The methods of data collction used were observation, interviews and documentations. The validity of the data uses technical triangulation. Data analysis techniques through three processes those are data reduction, data presentation and draw the conclution. According to analysis results, mathematical ability of students in solving PISA’s mathematic problem personal context st level 1 is very good, at level 2 dan level 3 is good, level 4 and level 5 is still a lack and at level 6 is the worst. The results of the research can be explained that mathematical ability of students in solving PISA’s mathematic problem personal context for level 1-3 is good and for level 4-6 still a lack.